Trading activity in the Indian government bond market - Michael J. Fleming; Seema Saggar; Samita Sareen (Federal Reserve Bank of New York, 2016)
We study how the Indian government bond market functions, how it has changed over time, and what factors help explain some of its features. Looking at the primary market, we describe how underwriting obligations are allocated to primary dealers via auction and identify several significant determinants of the underwriting commission cutoff rate, including the launch of the Negotiated Dealing System-Order Matching System (NDS-OM) electronic trading platform. Turning to the secondary market, we explore the importance of benchmark bonds, the launch of NDS-OM, the growth in trading activity, and the migration of activity from the over-the-counter (OTC) market to NDS-OM. We find that benchmark bonds, larger issues, and recently issued bonds tend to trade more actively, but that the launch of NDS-OM is associated with a reduced likelihood of a bond trading but greater trading volume conditional on trading. Benchmark bonds, larger issues, and recently issued bonds are associated with a greater share of NDS-OM trading volume (as opposed to OTC trading volume), suggesting that the NDS-OM platform is especially attractive for trading bonds with benchmark attributes.
Keywords: G12; G15; H63; 330; India; government bonds; trading activity